Health Service Utilization in Rural Areas of Edirne and Kırklareli - Gamze DEMİRAY; Mehmet GÜNEŞ; Burcu TOKUÇ; Muzaffer ESKiOCAK (Namık Kemal Tıp Dergisi)
Aim: This study aims to assess health service utilization and its correlation with socio-economic variables among rural residents of Edirne and Kırklareli provinces. Materials and Methods: This cross-sectional study was conducted between May and October 2019 with a survey in 414 households in 50 villages in Edirne and Kırklareli provinces. Data were collected via a 42-question questionnaire. Results: Of the visited villages, 36 (72%) lacked health institutions, while 5 (10%) had health centers and 9 (18%) had family health centers (FHC). During working hours, 50.2% preferred public hospitals, 37.2% favored FHC, and 9.2% chose private hospitals/practices. Notably, 64.5% of elderly participants with chronic conditions lacked regular follow-ups, along with 65.5% of women aged 15-49 years, while all children received regular care. Conclusion: Although access to healthcare services appears to be sufficient in the rural areas of Edirne and Kırklareli, located in the Thrace region, it has been observed that there is a dependency on demand-based services. Notably, consistent primary care follow-ups, excluding childhood, appear lacking, highlighting a gap in providing qualified and reliable health services to the public.